2022
DOI: 10.1212/cpj.0000000000200089
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functional Impairment and the Risk of Incident Mild Cognitive Impairment in an Observational Study of World Trade Center Responders

Abstract: Background and Objectives:Posttraumatic stress disorder (PTSD) has been linked to increased risk of cognitive dysfunction and physical functional impairment (PFI). The objective of this prospective cohort study was to examine whether PFI was associated with increased risk of incident mild cognitive impairment (MCI) among World Trade Center (WTC) responders with PTSD. We hypothesized that responders with PTSD would have an elevated risk of incident MCI, and that PFI would mediate this increase.Methods:We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Having MCI or dementia is associated with greater physical decline compared to older people with normal cognition [23]. Older adults with MCI converted to dementia more rapidly than those without physical functional impairment [24]. Older adults with MCI may develop Alzheimer's disease (AD) in approximately 3.5 years, and both cognitive and physical function may decline gradually after AD onset [25].…”
Section: Discussionmentioning
confidence: 99%
“…Having MCI or dementia is associated with greater physical decline compared to older people with normal cognition [23]. Older adults with MCI converted to dementia more rapidly than those without physical functional impairment [24]. Older adults with MCI may develop Alzheimer's disease (AD) in approximately 3.5 years, and both cognitive and physical function may decline gradually after AD onset [25].…”
Section: Discussionmentioning
confidence: 99%
“…Pellecchia et al found that Physical Functional Impairment (PFI) played an intermediary role in the relationship between Post-Traumatic Stress Disorder (PTSD) and Mild Cognitive Impairment (MCI). 7 The researchers mentioned that PFI may be the first sign of MCI in people with PTSD. Less physical movement increases the chances of diseases, disability, hospitalization, poorer quality of life, and death.…”
Section: Introductionmentioning
confidence: 99%